The 27th Chinese Control and Decision Conference (2015 CCDC) 2015
DOI: 10.1109/ccdc.2015.7161955
|View full text |Cite
|
Sign up to set email alerts
|

An inventory model with stochastic demand under conditionally permissible delay in payments

Abstract: Researchers in the past have established the newsvendor model with rarely considering trade credit. In practices, the supplier usually provides the retailer a permissible delay in payments to stimulate more order quantity. As a result, we try to establish an inventory model for stochastic demand, in which the supplier provides trade credit to the retailer if the order quantity is greater than or equal to a predetermined quantity. The residual or shortage at the end of the cycle is dealt as the newsvendor probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Pourmohammad Zia and Taleizadeh [9] established an EOQ inventory model with shortage under order-sizedependent advance and credit payments to optimize the ordering policy. Under order-quantity-dependent trade credit, Yueli et al [10] assumed the newsvendor model with stochastic demand and shortage and concluded that higher delay periods would increase the profit. When a three-echelon supply chain is assumed, Yang et al [11] obtained the maximum joint profit of a two-level trade credit for a single product with defective production and repair rate.…”
Section: Introductionmentioning
confidence: 99%
“…Pourmohammad Zia and Taleizadeh [9] established an EOQ inventory model with shortage under order-sizedependent advance and credit payments to optimize the ordering policy. Under order-quantity-dependent trade credit, Yueli et al [10] assumed the newsvendor model with stochastic demand and shortage and concluded that higher delay periods would increase the profit. When a three-echelon supply chain is assumed, Yang et al [11] obtained the maximum joint profit of a two-level trade credit for a single product with defective production and repair rate.…”
Section: Introductionmentioning
confidence: 99%